2021
DOI: 10.1186/s13075-021-02483-1
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid neutrophils in oligoarticular juvenile idiopathic arthritis have an altered phenotype and impaired effector functions

Abstract: Background Neutrophils are the most prevalent immune cells in the synovial fluid in inflamed joints of children with oligoarticular juvenile idiopathic arthritis (JIA). Despite this, little is known about neutrophil function at the site of inflammation in JIA and how local neutrophils contribute to disease pathogenesis. This study aimed to characterize the phenotype and function of synovial fluid neutrophils in oligoarticular JIA. Methods Neutrophi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…In line with this, our transwell-migrated non-suppressive neutrophils had impaired production of ROS and lower levels of NOX2 compared to non-migrated neutrophils. We have previously seen that oligoarticular JIA synovial fluid neutrophils tend to have impaired oxidative burst compared to neutrophils in the circulation ( 2 ), and low ROS production might be part of the explanation to why synovial neutrophils from several of the patients in this study are unable to suppress T cell proliferation. However, as ROS scavenging by catalase could only partly neutralize neutrophil-mediated inhibition of T cell proliferation, most likely other mechanisms for T cell suppression are also involved.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In line with this, our transwell-migrated non-suppressive neutrophils had impaired production of ROS and lower levels of NOX2 compared to non-migrated neutrophils. We have previously seen that oligoarticular JIA synovial fluid neutrophils tend to have impaired oxidative burst compared to neutrophils in the circulation ( 2 ), and low ROS production might be part of the explanation to why synovial neutrophils from several of the patients in this study are unable to suppress T cell proliferation. However, as ROS scavenging by catalase could only partly neutralize neutrophil-mediated inhibition of T cell proliferation, most likely other mechanisms for T cell suppression are also involved.…”
Section: Discussionmentioning
confidence: 65%
“…We have previously shown that neutrophils in JIA synovial fluid trend towards reduced oxidative burst compared to neutrophils in the blood ( 2 ), and we therefore sought to investigate if migration in our system would affect neutrophil ROS production. When exposed to PMA, neutrophils which had migrated towards synovial fluid had impaired ROS production compared to neutrophils incubated in the same synovial fluid ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Association with HLA class II and the presence of ANA suggests that an adaptive immune response is predominant in the pathogenesis of oligoarticular JIA. However, activated neutrophils with altered phenotype and dysfunction, and impaired synovial monocytes and macrophages with reduced capacity to phagocytose have recently been identified in synovial fluid of patients with oligoarticular JIA [ 28 , 29 ]. Together with high levels of monocyte-derived cytokines this emphasises the importance of the innate immune system in oligoarticular JIA pathogenesis [ 28 , 29 ].…”
Section: Pathogenesis Of Jiamentioning
confidence: 99%